2020
DOI: 10.1101/2020.08.28.272625
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-specific T-cell responses reflect substantive in vivo interactions with infected cells despite long-term therapy

Abstract: Antiretroviral therapies (ART) durably suppress HIV replication to undetectable levels – however, infection persists in the form of long-lived reservoirs of infected cells with integrated proviruses, that re-seed systemic replication if ART is interrupted. A central tenet of our current understanding of this persistence is that infected cells are shielded from immune recognition and elimination through a lack of antigen expression from proviruses. Efforts to cure HIV infection have therefore focused on reactiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…We saw remarkably similar responses for Nef-and Gag-specific IL-2producing CD4 1 and CD8 1 T cells following combination IC blockade. These data suggest that the effects of combination IC blockade extend to T cells that target either early or late viral gene products, although the frequency of Nef-specific T cells is highly stable on ART, whereas Gag-specific cells decay over time (41). There may be several explanations for the additive and synergistic effects with these Abs.…”
Section: Discussionmentioning
confidence: 96%
“…We saw remarkably similar responses for Nef-and Gag-specific IL-2producing CD4 1 and CD8 1 T cells following combination IC blockade. These data suggest that the effects of combination IC blockade extend to T cells that target either early or late viral gene products, although the frequency of Nef-specific T cells is highly stable on ART, whereas Gag-specific cells decay over time (41). There may be several explanations for the additive and synergistic effects with these Abs.…”
Section: Discussionmentioning
confidence: 96%
“…It is possible that intact genomes provide the infected cells with a selective advantage to escape immune-mediated killing during proliferation. In support of this model, it was recently shown that functional Nef plays a role in the persistence of genetically intact HIV [44] and that Nef-specific CD8+ T cells are associated with the frequencies of infected cells [75]. Alternatively, the higher clonality of the inducible viral reservoir may reflect the lower inducibility of HIV genomes in TCM cells, a subset previously shown to be more refractory to reactivation [76] and which is characterized by a greater clonotypic diversity [72].…”
Section: Discussionmentioning
confidence: 88%
“…Conversely, Nef can induce the expression of PD-1 on the surface of CD4 + T-cells in vitro (76). Recent studies have shown that the HIV-1 Nef protein is expressed during ART and can be produced from defective proviruses (46,47,77,78). Therefore, the presence of the HIV-1 Nef protein during ART may affect PD-1 and CTLA-4 expression on infected cells, in addition to the persistence of these infected cells.…”
Section: Discussionmentioning
confidence: 99%